2022
DOI: 10.1139/cjfas-2020-0412
|View full text |Cite
|
Sign up to set email alerts
|

The timing of spring warming shapes reproductive effort in a warm-water fish: the role of mismatches between hepatic and gonadal processes

Abstract: Spring-spawning fishes native to northern environments rely on both increasing temperature and lengthening photoperiod to cue reproduction and may thus be particularly sensitive to rapid warming earlier in the year while day lengths remain short. We investigated the reproductive response of pumpkinseed sunfish Lepomis gibbosus to spring warming commencing at a range of day lengths (9 – 15 hours), corresponding to various calendar days (January 10 – May 22). In both the laboratory and field, both male and femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Interestingly, two of the three studied populations exhibited increases in the size of the digestive tract during winter months when foraging was low. Such increases in gut size during low-temperature periods may facilitate the maintenance of digestive capacity when suboptimal temperatures would otherwise inhibit digestion [ 32 , 33 ], potentially fuelling reproductive preparation in the liver that can occur during the winter in pumpkinseed [ 34 ]. Similarly, maintaining digestive capacity during the winter may allow fish to use low levels of feeding to combat the depletion of energy reserves, assuming sufficient resources are available [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, two of the three studied populations exhibited increases in the size of the digestive tract during winter months when foraging was low. Such increases in gut size during low-temperature periods may facilitate the maintenance of digestive capacity when suboptimal temperatures would otherwise inhibit digestion [ 32 , 33 ], potentially fuelling reproductive preparation in the liver that can occur during the winter in pumpkinseed [ 34 ]. Similarly, maintaining digestive capacity during the winter may allow fish to use low levels of feeding to combat the depletion of energy reserves, assuming sufficient resources are available [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, this finding may be linked to food availability, a factor often correlated with temperature (reviewed in Hussain & Pandit, 2012). In natural systems, the expression of secondary sexual characteristics and body condition (optimal for gamete quality, especially in females; Fernandes et al ., 2022) is often acquired from food, which can vary between seasons (Heins et al ., 2004). A study by Bass (1995) demonstrated that the warming of stream water and lengthening of daylight in the springtime increased productivity and macroinvertebrate diversity ( i.e ., number of individuals and number of taxa) compared to other seasons.…”
Section: Discussionmentioning
confidence: 99%